Columbus, Georgia, 1865 : the last true battle of the Civil War - Misulia, Charles A., 1980- (University of Alabama Press, 2010)
"In this work, Charles A. Misulia, a lifelong student of the Civil War and expert on the Battle of Columbus, provides a comprehensive study of the Easter Sunday, April 16, 1865, conflict. The struggle occurred in the dark of night, extended over a mile and half through a series of forts and earthworks, and was finally decided in an encounter on a bridge a thousand feet in length. Misulia presents the first complete account of this battle, examining and recounting in depth not only the composition and actions of the contending forces, which numbered some three thousand men on each side, but meticulously detailing the effect of the engagement on the city of Columbus and its environs. As such, this book fills in an omission in the grand account of our cataclysmic national struggle and also adds a significant chapter to the history of an important regional city. In addition, Misulia bravely takes on the long-vexing question of which encounter should be seen as the last 'battle' of the Civil War and argues persuasively that Columbus, Georgia, qualifies for this distinction on a number of counts"--Flyleaf